Are All Tertiary Institutes in Hong Kong Ready to Provide Dyslexic Students with Suitable Special Examination Arrangements? (Asian Education Studies, 2016)
This paper discusses whether all tertiary institutes in Hong Kong are ready to provide dyslexic students with suitable special examination arrangements. Various challenges are identified. More efforts are warranted to establish a system with the necessary and appropriate professional support for analyzing the requests for examination arrangements. Only then can students with special educational needs truly benefit.